2006
DOI: 10.1086/498896
|View full text |Cite
|
Sign up to set email alerts
|

Hubble Space TelescopeImaging of the Outburst Site of M31 RV

Abstract: M31 RV is a luminous red variable star that appeared for several months in the bulge of M31 during 1988. Unlike classical novae, M31 RV was cool throughout its outburst. Interest in this object has been revived recently because of its strong resemblance to V838 Mon, a luminous Galactic variable star that appeared in 2002 and is illuminating a spectacular light echo, and has evolved to ever cooler surface temperatures. ( V4332 Sgr is a third object that was also a red supergiant throughout its eruption.) We hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Kato (2003) suggests that Nova CK Vul 1670 might have been a stellar merger event. Bond & Siegel (2005) mention that Nova V1148 Sgr 1943 had a late-type spectrum thus being a possible object of the V838 Mon type. It is quite probable that some V838 Mon type objects remain hidden among stars catalogued as classical nova or nova-like.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…Kato (2003) suggests that Nova CK Vul 1670 might have been a stellar merger event. Bond & Siegel (2005) mention that Nova V1148 Sgr 1943 had a late-type spectrum thus being a possible object of the V838 Mon type. It is quite probable that some V838 Mon type objects remain hidden among stars catalogued as classical nova or nova-like.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…Bond & Siegel (2006) examined the site of the eruption in Hubble Space Telescope images and reported that "there is no evidence for any significant young population at this location in the M31 bulge". M85-OT erupted near the lenticular galaxy (Hubble type S0) M85.…”
Section: Stellar Populationsmentioning
confidence: 99%
“…This is because they are restricted to a single type of stars, while the members in the V838 Mon class are of different kinds. It was concluded that the progenitor of V838 Mon is a B supergiant while that of V4332 Sgr, and most likely M31RV, are red giants (Tylenda et al 2005a; Bond & Siegel 2006). Therefore, only scenarios that use different types of stars could be invoked to explain their eruptions.…”
Section: Discussionmentioning
confidence: 99%
“…Soon after its outburst, V838 Mon was recognized as the prototype of a new class of stars (Munari et al 2002; Bond et al 2003), which currently consists of three objects: M31RV (Red Variable in M31 in 1988; Rich et al 1989; Mould et al 1990; Bryan & Royer 1992), V4332 Sgr (Luminous Variable in Sgr, 1994; Martini et al 1999) and V838 Mon (Peculiar Red Variable in 2002), plus three candidates – CK Vul, which was identified with an object that had a nova‐like event in the year 1670 (Shara & Moffat 1982; Shara, Moffat & Webbink 1985; Kato 2003; Retter & Marom 2003), V1148 Sgr, which had a nova outburst in 1943 and was reported to have a late‐type spectrum (Mayall 1949; Bond & Siegel 2006) and the peculiar variable in Crux that erupted in 2003 (Della Valle et al 2003).…”
Section: Introductionmentioning
confidence: 99%